A Case Report of Gorlin-goltz Syndrome - Nafarzadeh, Shima; Mozaffari, Fatemeh; Khakbaz, Oveis (Journal of Contemporary Medical Sciences, 2016)
Nevoid basal cell carcinoma syndrome (Gorlin syndrome) is an autosomal dominant inherited condition that exhibits high penetrance and variable expressivity. The syndrome is caused by mutations in patched (PTCH), a tumor suppressor gene that has been mapped to chromosome 9q22.3-q31. Gorlin-goltz syndrome (GGS) is characterised by the presence of multiple odontogenic keratocysts in the jaws, basal cell carcinomas, palmar and plantar pits and intracranial calcifications. Here, we present a case of familial GGS, characterised by multiple odontogenic keratocysts, broad nasal ridge, hypertelorism, enlarged head circumference and dermoid cysts.